Islam and Christianity : Theological Themes in Comparative Perspective - Renard, John, 1944- (Book collections on Project MUSE., 2011)
In light of the widespread public perception of incompatibility between Islam and Christianity, this book provides a much-needed straightforward comparison of these two great faith traditions from a broad theological perspective. Award-winning scholar John Renard illuminates the similarities as well as the differences between Islam and Christianity through a clear exploration of four major dimensions--historical, creedal, institutional, and ethical and spiritual. Throughout, the book features comparisons between concrete elements such as creedal statements, prayer texts, and writings from major. -- Publisher description.